PERILAKU HARIAN ELANG JAWA (Nisaetus bartelsi) DI KANDANG REHABILITASI PUSAT KONSERVASI ELANG KAMOJANG GARUT - Nurhayati Nurhayati; Iing Nasihin; Nurdin Nurdin (Journal of Forestry And Environment, 2022)
This research was done to find out the Javan eagle's daily habits, how long the rehabilitation process takes, and what factors influence the effectiveness of the procedure. The ad libitum approach is employed in this study, and every motion will be documented. Two birds with the names Mario and Tegar were the subject of the study. Compared to the Tegar individual, Mario, the Javan eagle, exhibits a behavior that is 51% more typical. The rate of hunting behavior is 51% in Mario individuals compared to 49% in Tegar individuals, which is higher. Mario people exhibit less social behavior than Tegar people: their respective rates are 49% and 51%, respectively. Hunting prowess and social behavior both necessary for life in the wild are the key elements in determining rehabilitation success. The process of rehabilitation is greatly influenced by environmental variables as well. The Javan eagle's rehabilitation will be interfered with by the volume of human activity near its cage. Mario and Tegar are still not ready to be released into the wild and still require rehabilitation because of some undesirable behaviors; if the eagle is released into the wild, it is anticipated.Penelitian ini dilakukan untuk mengetahui perilaku harian elang jawa, berapa lama waktu proses rehabilitasi dan faktor apa saja yang menjadi penentu keberhasilan. Metode yang digunakan yaituadlibitum, setiap pergerakan dicatat. Elang jawa yang diteliti berjumlah dua individu dengan nama Mario dan Tegar. Persentase perilaku berburu Tegar lebih kecil dari persentase berburu Mario yaitu 49% sedangkan Mario 51%. Persentase perilaku sosial Tegar lebih besar dari persentase sosial Mario yaitu sebanyak 51% sedangkan Tegar 49%. Persentase perilaku umum tegar lebih kecil dari persentase perilaku Mario yaitu sebanyak 49% sedangkan Mario 51%. Variabel yang jadi penentu kelayakan pelepasliaran yaitu kemampuan berburu dan perilaku sosial. Faktor lingkungan juga sangat berpengaruh pada proses rehabilitasi, banyaknya aktifitas manusia di sekitar kandang akan menghambat proses rehabilitasi. Mario dan Tegar masih belum siap dilepasliarkan dan masih membutuhkan waktu untuk proses rehabilitasi karena masih ada beberapa perilaku yang belum baik